1971
DOI: 10.1103/physrevc.4.2046
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Levels inCl34

Abstract: 22 levels of Cl+ below E"=4. 7 MeV are populated by the y-ray decay of the three reso-.nances at E& --1058, 1098, and 1121 keV in the reaction S33(p, y)C1+. These resonances, selected for study because of their dominant modes of p decay to levels above 2.7 MeV for which hmited prior data exist, were investigated with an 80-cm Ge(Li) detector, and with Ge(Li)-NaI coincidence and angular-correlation techniques. The results obtained for levels below 2.3 MeV are in general agreement with other recent work. A new r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Our results III and IV are not subject to the doubt regarding the shell-model df structure of the T=I, 3 and 4-levels in 34S/C1, specifically that expressed by Erskine et al [13], who suggested that the 4.62MeV 3-level in 34S could be of collective nature, and by Hyder and Harris [14], who suggested that the 6.21MeV TJ'=14-level in 3~C1 (the analog of the 6.42MeV level in 3aS) is of non-pure character. Hyder and Harris [14] compared their experimental M1 strengths for A T=I transitions in 34C1 with theoretical values calculated from an analytical expression by Prosser and Harris [15] for df shell-model states.…”
Section: Theoretical Resultssupporting
confidence: 54%
“…Our results III and IV are not subject to the doubt regarding the shell-model df structure of the T=I, 3 and 4-levels in 34S/C1, specifically that expressed by Erskine et al [13], who suggested that the 4.62MeV 3-level in 34S could be of collective nature, and by Hyder and Harris [14], who suggested that the 6.21MeV TJ'=14-level in 3~C1 (the analog of the 6.42MeV level in 3aS) is of non-pure character. Hyder and Harris [14] compared their experimental M1 strengths for A T=I transitions in 34C1 with theoretical values calculated from an analytical expression by Prosser and Harris [15] for df shell-model states.…”
Section: Theoretical Resultssupporting
confidence: 54%
“…Some resonance states in T l decay mainly to high-lying states in contrast to the normal decay mode, where the states decay to lower-lying states. The ED = 1 058 and 1 018 keV resonances studied by Hyder and Harris [3] and the E, = 1 121 keV resonance studied by Glaudemans et al [l] are of this type. The decays of These states are of the type d,!,f,,,, T=o.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast to this, the E, = 1 542 and 1 627 keV resonances decay to the highlying states. According to Hyder and Harris [3] the 4075 keV level populated strongly at Ep = 1 542 keV decays entirely to the 146 keV level. Three additional branches clearly seen in the Ep = 1 542 keV spectrum de-excite this state.…”
Section: Measurementsmentioning
confidence: 97%
See 2 more Smart Citations